New Insights into the Understanding of Gastrointestinal Dysmotility - Bodil Ohlsson; Sabina Janciauskiene (AboutScience Srl, 2007)
Our understanding of the physiology of digestion, absorption, secretion, and motility in the gastrointestinal tract has improved immensely. Today it is well established that the gross functions of the gastrointestinal tract depend on the coordination between the muscles, nerves and hormones. The enteric nervous system (ENS) is involved in most of the physiological and pathophysiological processes in the gastrointestinal tract. Therefore, clinical and experimental studies on the ENS provide the basis for a better understanding of the mechanisms involved in gastrointestinal disorders and promote the development of therapeutic options. This review outlines some of the current views on the role of the ENS and its related hormones in gastrointestinal motility.